Mycotoxins in Food and Beverages Iinnovations and Advances - Montet, Didier; Brabet, Catherine; Galindo, Sabine; Ray, Ramesh C. (Food biology series, 2021)
"Mycotoxins are secondary metabolites produced by fungi in a wide range of foods (cereals, peanut, tree nuts, dried fruits, coffee, cocoa, grapes, spices...) both in the field and after harvest, particularly during storage. They can also be found in processed foods of plant origin, or by transfer, in food products of animal (milk, eggs, meat and offal). Mycotoxins are of major concern since they can cause acute or chronic intoxications in both humans and animals which are sometimes fatal. Many countries, particularly in Europe, have set maximum acceptable levels for mycotoxins in food and feed"--